2022
DOI: 10.1080/10406638.2022.2041050
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electronic, Vibrational and Pharmacological Investigations of Highly Functionalized Diarylmethane Molecules Using DFT Calculations, Molecular Dynamics and Molecular Docking

Abstract: Present work describes the UV-Visible and FT-IR spectral behavior of highly functionalized diarylmethanes via theoretical investigations. Analyses of both theoretical and experimental UV data were in good agreement with the assigned bands. In addition, calculations pertaining to natural bond orbitals (NBOs) and mapped molecular electrostatic potential surface (MEPS) were also performed, revealing that the strongest hyperconjugative intramolecular interactions involves the p ⟶ p * , LP ⟶ r * and n ! p à transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In particular, it requires low energy sensitivity to changes in molecular structure caused by core position displacement of PEP [14]. The DFT technique in the Gaussian 09 software was used to compute the optimum geometries, vibration frequencies, and energies of the molecular structure of PEP [15]. Lee's-Yang-Parr correlation function was formed based on 6-311G(d,p) and SDD basic set based program package with DFT/B3LYP method.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, it requires low energy sensitivity to changes in molecular structure caused by core position displacement of PEP [14]. The DFT technique in the Gaussian 09 software was used to compute the optimum geometries, vibration frequencies, and energies of the molecular structure of PEP [15]. Lee's-Yang-Parr correlation function was formed based on 6-311G(d,p) and SDD basic set based program package with DFT/B3LYP method.…”
Section: Methodsmentioning
confidence: 99%
“…22 Furthermore, it was observed that the poly aromatic compounds with donor-acceptor cores have exceptional uorescence. [23][24][25][26][27][28][29] To highlight the photophysical characteristics of extended conjugation systems, we have synthesized phenyl substituted m-terphenyl scaffolds.…”
Section: Introductionmentioning
confidence: 99%